Farmers' knowledge, perceptions and management practices for termite pests of maize in southern Benin - Loko, L.E.Y.; Orobiyi, A.; Toffa, J.; Fagla, S.M.; Gavoedo, M.; Tamò, Manuele (Walter de Gruyter GmbH, 2019)
Termite (Isoptera: Termitidae) infestation is an important constraint of maize production in Benin. A survey of 300 households was conducted in 2018 throughout 30 villages in Southern Benin to evaluate farmers’ knowledge, perceptions and management practices of maize termite pests using focus group discussions and individual interviews with a semi-structured questionnaire. The results showed that for most of the farmers, maize is the most susceptible crop to termite attacks and the maturation developmental stage having the highest termite abundance and damage. A total of 43 different names of maize termite pests corresponding to 8 species were recorded in the study area. Size and colour were the main criteria used by farmers to classify and identify maize termite pests. Amitermes evuncifer was perceived as the most damaging to maize during vegetative and maturation stages, while Macrotermes bellicosus was perceived by famers (32.5%) as most damaging during seedling and flowering maize development stages. Erratic rainfall was perceived by maize producers as the most important factor favouring termite infestation in maize fields. The majority of the local maize is considered by farmers as susceptible to termites. The use of synthetic insecticides was the main method to control termites. Four of the 20 pesticides used by farmers have active ingredients that have been listed as highly hazardous (class Ib) by the World Health Organization (WHO). Farmers training on the danger and impact of misuse of insecticides on the development of termite insecticide resistance was recommended. The development of an integrated termite management strategy is discussed and the future research for its implementation identified.